National Neurotrauma Registry Data in Low- and Middle-Income Countries - Current Status and Future Requirements; Comment on "Neurotrauma Surveillance in National Registries of Low- and Middle-Income Countries: A Scoping Review and Comparative Analysis of Data Dictionaries" - Fiona Lecky (Kerman University of Medical Sciences, 2023)
Since 1990 National Trauma Registries, - taking the form of "not for profit" small and medium enterprises - have been integral to improvementsin major injury case fatality in high-income settings. This is laudable but unsatisfactory as globally most years of life lost to injury occur in low- and middle-income countries (LMICs). International Journal of Health Policy and Management, recently published a scoping review of neurotrauma registries in LMICs by Barthelemy et al; from this the commentary reflects on the state of the art and how these LMIC registries could be taken to "the next level" as meaningful tools for improving major injury patient care.